Improving Community Health Through Preventive Measures in Makassar - Susianti, Susianti; Fausyiah, Nurul; Akram, Musfira Azizah (Journal of Asian-african Focus in Health, 2024)
This study examined the impact of preventive health measures on community health outcomes in Makassar. Employing a quantitative approach, a cross-sectional survey was conducted with 400 adult residents to assess their engagement in preventive behaviors, including vaccination, regular health check-ups, physical activity, and healthy eating habits. The study also explored the relationship between these behaviors and self-reported health outcomes, such as the absence of chronic diseases and overall well-being. Descriptive and inferential statistical methods, including Pearson correlation, regression analysis, and ANOVA, were used to analyze the data. The findings revealed a significant positive correlation between preventive health behaviors and better health outcomes, with vaccination showing the strongest association. Additionally, higher engagement in physical activity and healthy eating was found to predict improved health, particularly among individuals with higher education and income levels. These results highlight the importance of promoting preventive health measures to improve public health in urban areas, especially in developing countries like Indonesia. This study contributes to the understanding of how socio-demographic factors influence health behaviors and outcomes in a specific urban context and underscores the need for targeted health interventions. The findings suggest that public health policies should focus on increasing awareness and participation in preventive health measures across diverse socio-economic groups to enhance community well-being.